A Constitution—Almost of Age? Public Role-play in the Construction of Religious and Related Rights in the Constitution of the Republic of South Africa, 1996. (2nd January 2016) - Du Plessis, Lourens
ABSTRACT: This article gauges, in the run-up to the twentieth birthday of the Constitution, the proven ability of South Africa's highest law to afford religious communities and institutions, as well as their individual members, meaningful opportunity for public role-play in the construction (that is, the interpretation and application) of religious and related rights in the Bill of Rights (Chapter 2 of the Constitution). A catalogue of constitutional provisions entrenching religious and related rights, as well as examples of how these rights have been invoked in selected constitutional cases, constitute the substance of the discussion. Just having assertible constitutional rights is in itself a public matter. Section 7(2) of the Constitution adds force to this contention, requiring the state not only to respect and protect, but also to promote and fulfil the rights (including the religious and related rights) in the Bill of Rights. These rights can moreover be enforced not only against the state and its organs, but against fellow individuals and non-state bodies too. It will be argued that (and shown how) publicness, as 'the quality of being public', is inevitably associated with having constitutional rights, availing oneself of (and asserting) them—also in, for instance, religious disputes and other doings. A public domain that helps sustain a dynamic, visible and progressive realisation of religious rights is assumedly also one allowing sufficient scope for the public role-play of religious adherents and institutions. The case studies in this article are meant, amongst other things, to help form an impression of the quality of the public domain in relation to religious practice in South Africa.